Summer Bird Blue - Bowman, Akemi Dawn (Simon Pulse, 2018)
After her sister and songwriting partner, Lee, dies in an automobile accident, seventeen-year-old Rumi is sent to Hawaii with an aunt she barely knows while she and her mother grieve separately.